Attacks on the Network Synchronization Systems Counteraction Method Implemented in the Software and Hardware Device «MARSH! 3.0» - Dmitry Anatolevich Melnikov; Vladislav Romanovich Petrov; Evgeny Vasilevich Dirienko; Anton Anatolevich Abramov; Ivan Alexandrovich Korsakov; Stanislav Sergeevich Kuzminov (Безопасность информационных технологий, 2013)
This paper proposes attacks on the network synchronization systems counteraction technique, method, algorithm and realizable aspects. The network synchronization systems are included in information technology systems or networks. This method is implemented in software and hardware device (means) «MARSH! 3.0» providing trusted session.